Importância dos fluxos de comércio exterior para as empresas industriais brasileiras - Eduardo Augusto Guimar\~aes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This paper focuses on the use of imported inputs and on the importance of export revenues to Brazilian manufacturing firms and points out the implications of these results from the viewpoint of the insertion of the Brazilian industry in global value chains. It is based on information from the Brazilian Institute of Geography and Statistics (IBGE) industrial database that has only been used as input to other research carried out by that institution. The paper also includes estimates of the effect of exchange rate fluctuation on the industrial firms' financial results.
10419/284901
Keywords: F1; F14; 330; input imports; imported input coefficients; export coefficients; trade liberalization; global value chain